Retrofit of heat exchanger network in a paper making industry - Tea, S. Y.; Abdul Manan, Zainuddin (Universiti Malaysia Sabah, 2003)
A retrofit design procedure based on conventional Pinch Analysis was used to investigate the economic potential of retrofitting an air heating system for a paper making industry. The retrofit design procedure includes targeting and design stages. The results show that significant energy reduction can be achieved with some modifications on the existing heat recovery system. Three economically feasible alternative heat exchanger networks (HEN) were identified successfully using Pinch Analysis. Economic analysis was performed to access the benefits of the retrofitted HEN.